Consumer search and stock-out: A laboratory experiment - Yuta Kittaka; Ryo Mikami (Osaka University, Institute of Social and Economic Research (ISER), 2020)
We investigate the overall impact of stock-out on individual consumers' information search behavior through both search-theoretic and experimental approaches. As the probability of stock-out increases, search intensity decreases, while the expected number of searches may increase. Such increases in stock-out probability also deter consumers from participating in the market.
Keywords: C91; D11; D43; D83; L13; 330; consumer search; stock-out; search experiment; consumer behavior